ICT's and community media process documentation of setting-up an enhanced community communication station - Osalla, Ma. Teresita B. (The Philippine Journal of Development Communication, 2009)
The process documentation focused on how the Community Communication Station or CCS (a center where a personal computer with Internet connection was set-up) in Sitio Maligaya, Pagsawitan, Sta. Cruz, Laguna, Philippines enhanced the broadcast of the "Ugnayan at Balikatan" program of the Radio DLZB - the educational radio station of the University of the Philippines Los Baños. Overall, the CCS facilitated community members' participation in the radio program, made the broadcast attuned to listeners' needs and interest, and made them supportive of their community's development. In operating the CCS, community members must be allowed to appreciate, test, and develop deeper value of the ICT facilities, and be assured of their benefits before they could be expected to participate in the radio broadcast. An enhanced CCS must include a technical working group composed of various experts, a core group of community members who would manage the CCS, and a website manager, among others. The CCS technical set-up need not be complicated but one that would provide them an efficient Internet connection for a real-time access to the radio program.